2017
DOI: 10.1007/s12672-017-0316-3
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Epithelial-Mesenchymal Transition (EMT) and the Thyroid Hormones-αvβ3 Axis in Ovarian Cancer

Abstract: Ovarian cancer is a highly metastatic disease. The metastatic potential is enhanced by epithelial to mesenchymal transition (EMT) in which αvβ3 integrin plays a role. Thyroid hormones (L-thyroxine, T4, and 3,5,3'-triiodo-L-thyronine, T3) bind this integrin, and we hypothesized that the thyroid hormone-αvβ3 axis may be involved in EMT activity in ovarian cancer. The transcription (mRNA), protein abundance (westerns), and protein localization (fluorescence microscopy) of several EMT markers were studied in ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 78 publications
0
33
0
Order By: Relevance
“…Recently, the interplay between epithelial-mesenchymal transition (EMT) and the thyroid hormones-αvβ3 axis in ovarian cancer was investigated (Weingarten et al 2018). It was shown that the transcription of mesenchymal markers, β-catenin, zeb-1, slug/snail, vimentin, and n-cadherin was hardly affected by T3 and T4, while that of the epithelial markers, e-cadherin and zo-1, and was inhibited after treatment with thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the interplay between epithelial-mesenchymal transition (EMT) and the thyroid hormones-αvβ3 axis in ovarian cancer was investigated (Weingarten et al 2018). It was shown that the transcription of mesenchymal markers, β-catenin, zeb-1, slug/snail, vimentin, and n-cadherin was hardly affected by T3 and T4, while that of the epithelial markers, e-cadherin and zo-1, and was inhibited after treatment with thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…The link of thyroid hormone, particularly T4, to the EMT has recently been examined [ 17 ]. EMT is a cog in the mechanism of metastasis, accounting for the genesis of cells capable of metastasizing [ 33 ].…”
Section: Cancer Metastasis-relevant Molecular Mechanisms Of Thyroimentioning
confidence: 99%
“…Integrin αvβ3 and its T4 receptor have also been implicated in the process of cancer metastasis [ 16 , 17 , 18 ]. Tetrac in its small molecule formulation acts as a T4 antagonist at the αvβ3 integrin [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the transcription of mesenchymal markers, β-catenin, zeb-1, slug/snail, vimentin, and n-cadherin was hardly affected by T3 and T4, while that of the epithelial markers, e-cadherin and zo-1, and was inhibited after treatment with thyroid hormones. These results suggest a novel role for the thyroid hormone-αvβ3 axis in EMT, with possible implications for ovarian cancer metastasis [47].…”
Section: Discussionmentioning
confidence: 78%
“…Recently, the interplay between epithelial-mesenchymal transition (EMT) and the thyroid hormones-αvβ3 axis in ovarian cancer was investigated [47]. It was found that the transcription of mesenchymal markers, β-catenin, zeb-1, slug/snail, vimentin, and n-cadherin was hardly affected by T3 and T4, while that of the epithelial markers, e-cadherin and zo-1, and was inhibited after treatment with thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%